Analisis Kinerja Bongkar Muat Peti Kemas Berdasarkan Perbandingan Effective Time dan Berthing Time di PT. Kaltim Kariangau Terminal - Rifkah Fitriah; Andi Asniar; Arif Fuddin Usman; Muslihati Muslihati; A.Rachmianty A.M (Pusat Riset dan Inovasi Nasional, 2024)
Terminal Kaltim Kariangau is an institution engaged in port services. This study aims to analyze the loading and unloading performance in terms of the indicator of effective time compared to berthing time (ET:BT) in container loading and unloading services.This research uses data collection methods through interviewees, observations, and document studies, utilizing the interactive and qualitative data analysis model by Miles and Huberman.. The results of the study indicate that the ET:BT performance is categorized as good, in accordance with the standard set by the Director General of Sea Transportation at 70%. In 2022, the achievement of ET:BT was 70.70%, showing a slight decrease compared to 72.48% in 2021. This decrease is due to 197 out of 471 ship calls in 2022, or approximately 42%, not meeting the standard with an ET:BT value of 60.70%. Ship performance that does not meet the standard can be related to high values of NOT (Not operating time), IT (Idle Time), and waiting time for pilotage.